Nonpositive solutions to a certain functional differential inequality - Lomtatidze, A.; Opluštil, Z.; Šremr, J. (Нелінійні коливання, 2009)
In the paper, efficient conditions are found guaranteeing that every solution to the problem u'(t) ≥ ι(u)(t), u(a) ≥ h(u) is nonpositive, where ι : C([a, b]; R) → L([a, b]; R) and h : C([a, b]; R) → R are linear bounded operators. The results obtained are very useful for the investigation of the question on solvability and unique solvability of the nonlocal boundary-value problems for the first order functional differential equations in both linear and nonlinear cases.